Progression-free survival is an adequate endpoint for clinical trials of locally advanced and metastatic urothelial carcinoma. Issue 5 (15th September 2022) - Martini, Alberto; Fallara, Giuseppe; Ploussard, Guillaume; Pradere, Benjamin
Abstract : Purpose of review: To evaluate intermediate clinical endpoints that have been proposed as potential surrogates for overall survival amongst patients with locally advanced and metastatic urothelial carcinoma. Recent findings: Several endpoints have been proposed as potential surrogates for overall survival. They are: pathologic downstaging or complete response after neoadjuvant treatments and progression-free survival in the adjuvant setting and metastatic setting. Formal surrogacy, as per Prentice, has not been established among any of the aforementioned intermediate clinical endpoints and overall survival. Despite that, regulatory agencies have recently approved adjuvant nivolumab for patients with high-risk muscle invasive bladder cancer, based on the results of a trial that had disease-free survival as primary endpoint. Summary: Despite the lack of proven surrogacy between progression-free survival and overall survival, this endpoint seems adequate for trial design and medication approval, as the recent case of adjuvant nivolumab demonstrates.